"I Feel Like More of a Man": A Mixed Methods Study of Masculinity, Sexual Performance, and Circumcision for HIV Prevention. Issue 1 (2nd January 2017) - Fleming, Paul J.; Barrington, Clare; Pearce, Lisa D.; Lerebours, Leonel; Donastorg, Yeycy; Brito, Maximo O.
Abstract : Ethnographic studies from numerous societies have documented the central role of male circumcision in conferring masculinity and preparing boys for adult male sexuality. Despite this link between masculinity, sexuality, and circumcision, there has been little research on these dynamics among men who have been circumcised for HIV prevention. We employed a mixed methods approach with data collected from recently circumcised men in the Dominican Republic (DR) to explore this link. We analyzed survey data collected six to 12 months post-circumcision ( N  = 293) as well as in-depth interviews conducted with a subsample of those men ( n  = 30). We found that 42% of men felt more masculine post-circumcision. In multivariate analysis, feeling more masculine was associated with greater concern about being perceived as masculine (OR = 1.70, 95% CI: 1.25–2.32), feeling more potent erections post-circumcision (OR = 2.25, 95% CI: 1.26–4.03), and reporting increased ability to satisfy their partners post-circumcision (OR = 2.30, 95% CI: 1.11–4.77). In qualitative interviews, these factors were all related to masculine norms of sexually satisfying one's partner, and men's experiences of circumcision were shaped by social norms of masculinity. This study highlights that circumcision is not simply a biomedical intervention and that circumcision programs need to incorporate considerations of masculine norms and male sexuality into their programming.